UNCERTAINTY REDUCTION PROCESS MEMBERS OF VIRTUAL COMMUNITY TOKO BAGUS AREK AREK TEMANGGUNG ON FACEBOOK - Deny Firmansyah; Daru Purnomo; Dewi Kartika Sari (Universitas Kristen Satya Wacana, 2019)
Science and technology in the field of communication is increasingly growing rapidly, the more continuous era then the internet can join in the process of development that exists. The Internet is able to provide a variety of things that people need, both work and daily needs. The need for example is looking for news, looking for video, or other audio, the internet is able to provide the whole to be accessible by humans. Another example that can be done internet is an online-based buying, where the process of buying and selling can be done with a long distance but shorter time taken, wherever and whenever the human origin has internet access. But with access in a very fast time, there are also many online based fraud. Fraud is among others the goods and explanations of the seller is not the same, or the buyer who bought the goods was not serious to buy. This creates a sense of uncertainty from sellers and buyers when they want to sell or buy goods. Therefore, in this study, researchers try to discuss about the sense of reduction of uncertainty of the process of buying and selling online from both parties, both from the seller and from the buyer's position specifically on the Facebook group TOBAT Temanggung. The method used in this research is descriptive qualitative approach. The results of this study indicate that the process of sense of uncertainty reduction in TOBAT able to overcome uncertainty to decrease by using Unrcertainty Reduction Theory. By using several stages of the axioms applied to URT, both sellers and buyers have several distinctive characters to reduce the sense of uncertainty when buying and selling processes in the TOBAT virtual community on Temanggung Facebook.